Analysis for e-commerce protocols based on ProVerif - GUO Yun-chuan1; DING Li3; ZHOU Yuan3; GUO Li1 (Tongxin xuebao)
It was very important to analyze e-commerce protocols by formal methods.A technique for modeling the fair-change e-commerce protocol（FEEP） with automated dispute resolution and for verifying its property was proposed.First, FEEP was modeled in applied picalculus and a novel formalization of the fairness was provided in term of a correspondence property.Then, ProVerif, proposed by Juels, Catalano and Jakobsson, was adopted to analyze FEEP automatically.The results show that:it is feasible to formalize the fairness based on a correspondence property;ProVerif can be used to verify the property that before event A happened, event B had happened, but it is not applicable to analyze the property that after event A happened, event B would happen.